Synthesis of 13C-Labeled Steroids - Dénès, Fabrice; Farard, Julien; Lebreton, Jacques (Synthesis, 2019)
Due to the wide spectrum of biological activities of steroids, the detection and quantification of steroidal residues in various biological materials are crucial for drug development, doping prevention, and environmental protection. In addition, the analytical technique of stable isotopic dilution (SID) by Liquid Chromatography-Mass Spectrometry (LC-MS) requires 13C-labeled steroids as standards to provide accurate and reproducible steroid quantification. In this context, the synthesis of 13C-labeled steroids is reviewed. The approaches based on partial synthesis starting from commercially available steroids have been, by far, the most commonly employed strategy.1 Introduction2 Hemisynthesis of 13C3-Labeled Steroids via Partial Degradation of the A Ring2.1 Degradation of the A Ring to an Enol Lactone2.1.1 Introduction of 13C Atom(s) via Claisen Condensation: Turner’s Strategy2.1.2 Introduction of 13C Atom(s) with 13C-Labeled 5-(Diethylphosphono)pentan-2-one Ethylene Ketal Based on the Fujimoto–Belleau Reaction2.2 Degradation of the A Ring and Introduction of 13C Atom(s) with [13C3]-1-(Triphenylphosphoranylidene)propan-2-one3 Construction of the A Ring from an α,β-Unsaturated Ketone with 13C-Labeled 1-Iodo-3,3-(ethylenedioxy)butane as Electrophile4 Construction of the A and B rings: Stork’s Strategy5 Hemisynthesis with Introduction of 13C Atom(s) in the C17 Side Chain6 Conclusion
Keywords: steroids; 13C-labeled compounds; hemisynthesis; stable isotope labeling